Analisis Scanning Electron Microscope (SEM) Mikroarsitektur Daerah Metafisis Os Femur Tikus Putih (Rattus novergicus) Ovariohisterektomi dengan Pemberian Madu Lebah (Apis dorsata) Hutan Sumbawa - Samsi Yordan; Abdullah Hasib; Muhammad Huda Ramadhan Ibrahim; Siti Nur Rohmah; Salsabilla Abani; Ira Sari Yudaniayanti (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2018)
The aims of this study to determine the effect of honey bees (Apis dorsata) to prevent the decrease of femur density in ovariohysterctomized rats as animal model of osteoporosis by Scanning Electron Microscope (SEM). This study used 20 adult female white rats (Rattus norvegicus) with body weight 300 gr. Divided into 5 groups, negative control group (P0-), not in ovariohysterectomy, only given aquadest 1.5 ml/day ; Positive control group (P0 +), in ovariohysterectomy, only given aquadest 1.5 ml/day; Treatment group 1 (P1), in ovariohysterectomy and given honey 1 gram / kg BB + 1.5 ml aquadest; Treatment group 2 (P2), in ovariohysterectomy and given honey 2 grams / kg BB + 1.5 ml aquadest; Treatment group 3 (P3), in ovariohysterectomy and given honey 4 grams / kg BB + 1.5 ml aquadest. After 12 weeks, all rats were sacrified for removal of the femur and performed by SEM. Analysis of SEM showed that mice administered honey with a dose of 4 grams / kg BW (P3) showed bone density approaching negative control treatment (P0-), ie, ovariohysterectomized rats. P3 showed the most less bone porosity than other treatment groups. The largest and most uniformly distributed porosity was shown by the positive control group (P0 +). The best results with the smallest quantity and size of the porosity of femur is in P3 group. In conclusion, honey (Apis dorsata) can prevent the decrease in bone density of the femur by Scanning Electron Microscope (SEM).